Clinical characteristics, Cryptococcus neoformans genotypes, antifungal susceptibility, and outcomes in human immunodeficiency virus-positive patients in Beijing, China. Issue 5 (May 2021) - Xu, Xinmin; Du, Pengcheng; Wang, Huizhu; Yang, Xiaoling; Liu, Tingting; Zhang, Yuanyuan; Wang, Yajie
Cryptococcus neoformans is an environmental fungal pathogen that causes opportunistic infections and severe disseminated meningoencephalitis, mainly in immunocompromised patients such as those with acquired immunodeficiency syndrome (AIDS). In this study, the clinical characteristics, treatment protocols, and outcomes of 70 patients with AIDS and Cryptococcus neoformans infection at Beijing Ditan Hospital were retrospectively analyzed. We performed antimicrobial sensitivity tests and multilocus sequence typing (MLST) on C. neoformans isolates from these patients. The most common symptoms were headache (58.6%), fever (54.3%), and high cerebrospinal fluid pressure (≥200 mm H2 O) (71.4%). All patients were positive for C. neoformans antigen in blood or cerebrospinal fluid. The CD4 cell counts of 92.8% (65/70) of patients were <100 cells/µL. In total, 74 C. neoformans isolates were obtained from the 70 patients. The 65 isolates that could be typed fell into 12 sequence types (STs) by MLST: ST5, ST31, ST63, ST202, ST237, ST289, ST295, ST296, ST298, ST324, ST337, and ST359. ST5 was the major type, accounting for 78.5% of isolates (51/65). This study comprehensively assessed the clinical and molecular epidemiology of C. neoformans in patients with AIDS and may inform the development of targeted prevention and treatment strategies for immunocompromised patients with C. neoformans infection.